Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine which of the given summations represent the series 11, 17, 23, and 29, we need to evaluate each summation for the specified values of [tex]\( n \)[/tex].
Let's consider each summation one by one:
### 1. [tex]\(\sum_{n=1}^4(5n+6)\)[/tex]
Evaluate the expression [tex]\(5n + 6\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 5(1) + 6 = 5 + 6 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 5(2) + 6 = 10 + 6 = 16\)[/tex]
- For [tex]\(n = 3: \qquad 5(3) + 6 = 15 + 6 = 21\)[/tex]
- For [tex]\(n = 4: \qquad 5(4) + 6 = 20 + 6 = 26\)[/tex]
The resulting series is [tex]\(11, 16, 21, 26\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### 2. [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
Evaluate the expression [tex]\(6n + 5\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 3: \qquad 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 4: \qquad 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 3. [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n+1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0+1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 1: \qquad 6(1+1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 2: \qquad 6(2+1) + 5 = 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 3: \qquad 6(3+1) + 5 = 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 4. [tex]\(\sum_{n=0}^3(6(n-1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n-1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0-1) + 5 = 6(-1) + 5 = -6 + 5 = -1\)[/tex]
- For [tex]\(n = 1: \qquad 6(1-1) + 5 = 6(0) + 5 = 0 + 5 = 5\)[/tex]
- For [tex]\(n = 2: \qquad 6(2-1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 3: \qquad 6(3-1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
The resulting series is [tex]\(-1, 5, 11, 17\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### Conclusion
The summations that represent the series [tex]\(11, 17, 23, 29\)[/tex] are:
- [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
- [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Let's consider each summation one by one:
### 1. [tex]\(\sum_{n=1}^4(5n+6)\)[/tex]
Evaluate the expression [tex]\(5n + 6\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 5(1) + 6 = 5 + 6 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 5(2) + 6 = 10 + 6 = 16\)[/tex]
- For [tex]\(n = 3: \qquad 5(3) + 6 = 15 + 6 = 21\)[/tex]
- For [tex]\(n = 4: \qquad 5(4) + 6 = 20 + 6 = 26\)[/tex]
The resulting series is [tex]\(11, 16, 21, 26\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### 2. [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
Evaluate the expression [tex]\(6n + 5\)[/tex] for [tex]\(n = 1, 2, 3, \text{and} 4\)[/tex]:
- For [tex]\(n = 1: \qquad 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 2: \qquad 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 3: \qquad 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 4: \qquad 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 3. [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n+1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0+1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 1: \qquad 6(1+1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
- For [tex]\(n = 2: \qquad 6(2+1) + 5 = 6(3) + 5 = 18 + 5 = 23\)[/tex]
- For [tex]\(n = 3: \qquad 6(3+1) + 5 = 6(4) + 5 = 24 + 5 = 29\)[/tex]
The resulting series is [tex]\(11, 17, 23, 29\)[/tex], which matches the target series. Thus, this summation represents the series.
### 4. [tex]\(\sum_{n=0}^3(6(n-1)+5)\)[/tex]
Evaluate the expression [tex]\(6(n-1) + 5\)[/tex] for [tex]\(n = 0, 1, 2, \text{and} 3\)[/tex]:
- For [tex]\(n = 0: \qquad 6(0-1) + 5 = 6(-1) + 5 = -6 + 5 = -1\)[/tex]
- For [tex]\(n = 1: \qquad 6(1-1) + 5 = 6(0) + 5 = 0 + 5 = 5\)[/tex]
- For [tex]\(n = 2: \qquad 6(2-1) + 5 = 6(1) + 5 = 6 + 5 = 11\)[/tex]
- For [tex]\(n = 3: \qquad 6(3-1) + 5 = 6(2) + 5 = 12 + 5 = 17\)[/tex]
The resulting series is [tex]\(-1, 5, 11, 17\)[/tex], which does not match [tex]\(11, 17, 23, 29\)[/tex]. Therefore, this summation does not represent the series.
### Conclusion
The summations that represent the series [tex]\(11, 17, 23, 29\)[/tex] are:
- [tex]\(\sum_{n=1}^4(6n+5)\)[/tex]
- [tex]\(\sum_{n=0}^3(6(n+1)+5)\)[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.